A Design Method to Increase the Bandwidth of Reflectarray Antennas - Christos Exadaktylos; Anastasios G. Koutinos; Constantinos L. Zekios; Stavros V. Georgakopoulos (IEEE Open Journal of Antennas and Propagation)
This work introduces a novel design methodology to redesign traditional reflectarray antennas (RAs) with bandwidths in the order of 15% and double their bandwidth without increasing their design complexity. A wideband RA unit cell (UC) is designed utilizing multiple connection points between the radiating and phase shifting structure. Notably, to properly set the desired phase shift at each UC of the RA aperture across the entire frequency band, true-time-delay (TTD) lines are connected to each element. To validate the performance of our proposed approach a traditional microstrip patch-based RA is used as an example. By applying our proposed method to this RA, we develop a design that achieves a fractional 1.5 dB gain bandwidth of 31% (8.6 GHz to 11.8 GHz) in the X-band, which is more than two times larger than the 14% fractional bandwidth of the traditional RA design. Our RA is prototyped to validate its performance. The measurements show excellent agreement with simulations thereby validating our proposed methodology.